Narratology and text : subjectivity and identity in New France and Québécois literature - Perron, Paul (Toronto studies in semiotics and communication., 2003)
In Narratology and Text, Paul Perron examines the role that literature plays in the formation of French Canadian identity. Perron presents a narratological and semiotic analysis of canonical non-fictional and fictional texts from New France and Quebec, and illustrates how citizens of French Catholic origins living in Canada have constructed their identity by defining the self as part of a closed community founded in race, language, and religion, and as radically opposed to the other, constituted as an omnipresent heterogeneous threat to the homogenous group. The first section of Perron's study is devoted to an historico-notional overview of some of the major contributors to the theory of narrative, especially that of A.J. Greimas. The second and third parts initially examine the primary and founding texts of first encounters, Jacques Cartier's Voyages of 1534 and 1535, and the Jesuit Relations, and then turn to discussions of six representative Québécois novels from the mid-nineteenth century to the end of the Duplessis era. Each work is examined in terms of its definitions of the self, the other, the group, the nation, language, race, and religion, as well as its treatment of the idea of place - the utopian here as opposed to a dystopian there or elsewhere. Fusing semiotics, narratology, stylistics, and literary and cultural theory with one of the only English-language studies on Greimas, this important work offers an original and thought-provoking contribution to studies of literature and semiotics.